Serial Diffusion-Weighted MR Imaging and Proton MR Spectroscopy of Acute Large Demyelinating Brain Lesions: Case Report - Rovira, Alex; Pericot, Imma; Alonso, Juli; Rio, Jordi; Grivé, Elisenda; Montalban, Xavier (American Journal of Neuroradiology, 2002)
Summary: We present the serial MR studies of two patients with symptomatic acute large demyelinating lesions that initially showed a drop in apparent diffusion coefficient values. Baseline proton MR spectroscopy showed a slight decrease in N-acetylaspartate and a normal choline level. An excess of lactate was observed at the first examinations and completely disappeared by the final examinations.The time-course evolution of the lesions shown by MR imaging and proton MR spectroscopic examinations suggests that the initial drop in apparent coefficient diffusion may have been related to dense inflammatory cell infiltration and scant tissue destruction or to reversible reduced vascular supply due to the severity of the inflammatory process.